Hot rod hamster! - Lord, Cynthia; Anderson, Derek, 1969- (New York : Scholastic Press, 2010)
A hamster, with the help of a canine junkyard dealer and his mouse assistants, builds a hot rod and drives it in a race against some very large dogs.
School Library Journal, January 2010
Publisher's Weekly, January 2010
Booklist, December 2009
Kirkus Review, December 2009
1.9
K-3
Keywords: Automobiles -- Juvenile fiction; Automobile racing -- Juvenile fiction; Hamsters -- Juvenile fiction; Dogs -- Juvenile fiction; Mice -- Juvenile fiction; Automobiles -- Fiction; Automobile racing -- Fiction; Hamsters -- Fiction; Dogs -- Fiction; Mice -- Fiction; Automobiles -- Fiction; Automobile racing -- Fiction; Hamsters -- Fiction; Dogs -- Fiction; Mice -- Fiction; Picture books for children